2020
DOI: 10.1002/cbin.11529
|View full text |Cite
|
Sign up to set email alerts
|

Functional damage of endothelial progenitor cells is attenuated by 14‐3‐3‐n through inhibition of mitochondrial injury and oxidative stress

Abstract: Endothelial progenitor cells (EPCs) are precursor cells of vascular endothelial cells, which are widely involved in the pathological process of cardiovascular diseases. EPCs apoptosis could accelerate the process of cardiovascular diseases. 14-3-3-η protein has been proved to be a potent antiapoptosis molecule. However, inhibition of EPCs apoptosis by 14-3-3-η and further specific mechanism have not been investigated. EPCs were isolated from human cord blood, and identified using VEGFR2 and CD34. 14-3-3-η over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Among 14‐3‐3 family members, 14‐3‐3‐η has been reported to be a diagnostic marker for rheumatoid arthritis (RA) (Maksymowych, Naides, et al, 2014, Maksymowych, van der Heijde, et al, 2014), but its precise function in RA and other biological processes is not well defined. Recently, we reported that 14‐3‐3‐η overexpression can inhibit ox‐LDL‐induced apoptosis and oxidative stress in EPCs (Li et al, 2021), and a similar finding was also reported in mouse cardiomyocytes (Sreedhar et al, 2015). However, the mechanism by which 14‐3‐3‐η antagonizes the effect of ox‐LDL on EPCs remains unknown.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Among 14‐3‐3 family members, 14‐3‐3‐η has been reported to be a diagnostic marker for rheumatoid arthritis (RA) (Maksymowych, Naides, et al, 2014, Maksymowych, van der Heijde, et al, 2014), but its precise function in RA and other biological processes is not well defined. Recently, we reported that 14‐3‐3‐η overexpression can inhibit ox‐LDL‐induced apoptosis and oxidative stress in EPCs (Li et al, 2021), and a similar finding was also reported in mouse cardiomyocytes (Sreedhar et al, 2015). However, the mechanism by which 14‐3‐3‐η antagonizes the effect of ox‐LDL on EPCs remains unknown.…”
Section: Introductionsupporting
confidence: 74%
“…The isolation of EPC was carried out as previously described (Li et al, 2021). In brief, 30 mL cord blood was collected from each full-term healthy parturient woman and was subjected to density gradient centrifugation to isolate mononuclear cells, which were plated into fibronectin-coated six-well culture plates at a density of 5 × 10 5 cells/cm 2 .…”
Section: Isolation Culture and Characterization Of Epcsmentioning
confidence: 99%
“…The makers were entered into MetaboAnalyst to determine the impacted metabolism related pathways. 1 The Data analysis method is consistent with the previous publication ( 16 ).…”
Section: Methodssupporting
confidence: 63%
“…Network pharmacology analysis and experimental validation also showed that DHI attenuates doxorubicin-induced cardiotoxicity in rats via suppression of apoptosis ( 15 ). Furthermore, its ability to improve cardiac function, reduce myocardial injury, and enhance vascular endothelial function has been reported in both animal and clinical studies ( 8 , 16 ).…”
Section: Introductionmentioning
confidence: 99%